(untitled) (Clinics, 2021)
OBJECTIVES: We sought to analyze the hemodynamic effects of the multilayer flow-modulated stent (MFMS) in Thoracoabdominal aortic aneurysms (TAAAs). METHODS: The hemodynamic effects of MFMS were analyzed in aortic thoracoabdominal aneurysms in experimental swine models. We randomly assigned 18 pigs to the stent or control groups and underwent the creation of an artificial bovine pericardium transrenal aneurysm. In the stent group, an MFMS (Cardiatis, Isnes, Belgium) was immediately implanted. After 4 weeks, we evaluated aneurysm sac thrombosis and renal branch patency by angiography, duplex scan, and morphological analysis. RESULTS: All the renal arteries remained patent after re-evaluation in both groups. Aneurysmal sac thrombosis was absent in the control group, whereas in the stent group it was present in 66.7% of aneurysmal sacs (p=0.061). The mean final aneurysm sac diameter was significantly lower in the stent group (mean estimated reduction, 6.90 mm; p=0.021). The proximal neck diameter decreased significantly in the stent group (mean difference, 2.51 mm; p=0.022) and grew significantly in the control group (mean difference, 3.02 mm; p=0.007). The distal neck diameter increased significantly in the control group (mean difference, 3.24 mm; p=0.017). There were no significant findings regarding distal neck measurements in the stent group. CONCLUSION: The MFMSs remained patent and did not obstruct the renal arteries within 4 weeks. In the stent group, the device was also associated with a significant decrease in aneurysmal sac diameter and a large proportion (albeit non-significant) of aneurysmal sac thrombosis.